Experimental and Theoretical Investigations of Complex Formation of Substituted Phenylazo-Derivatives of Methylphloroglucinol - Kovalchukova, Olga; A.T., Amangdam; S.B., Strashnova; P.V., Strashnov; E.P., Romashkina; O.V., Volyansky (JOURNAL OF ADVANCES IN CHEMISTRY, 2013)
Using spectrophotometric titration technique, the processes of complex formation of some phenylazo-derivatives of methylphloroglucinol (MPG) containing hydroxo-, nitro- and nitroso-substituents were studied. The spectral criteria of neutral and ionized forms of the organic ligands in their different tautomeric forms were determined. It was detected that the complex formation is accompanied by formation of one or two chelate cycles which involve azo- or nitroso-fragments and neighboring OH-groups of the organic ligands. Different types of coordination lead to different changes in the electronic absorption spectra. The DFT-B3LYP modeling of a Ni(II) complex of Î±-hydroxyphenylazo MPG established the most probable coordination mode of the organic ligand: tridentate chelating dianion, distorted square coordination of Ni-cations including one water molecule.Â The theoretical results are in a good accordance with the experimental data.